α-Galactosidase Activity of Lactobacilli - Mital, B. K. (1973)
α-Galactosidase (EC 3.2.1.22) activity was observed in cell-free extracts of Lactobacillus fermenti, L. brevis, L. buchneri, L. cellobiosis, and L. salivarius subsp. salivarius. The cultural conditions under which the enzyme activity was detected suggest that the enzyme is constitutive and present in the soluble fraction in the cell. The enzyme preparations readily hydrolyzed melibiose and other oligosaccharides containing α(1 → 6) linked galactose. Although the cell-free extracts of L. fermenti and L. brevis are negative for β-fructofuranosidase (EC 3.2.1.26), they hydrolyzed melibiose, stachyose, and raffinose in decreasing order of activity. The β-fructofuranosidase-positive L. buchneri, L. cellobiosis, and L. salivarius preparations hydrolyzed melibiose, raffinose, and stachyose in decreasing rates of activity. The α-galactosidases from different lactobacilli showed optimum activity in pH range 5.2 to 5.9. L. fermenti and L. salivarius preparations exhibited maximum activity between 40 to 44 C and 48 to 51 C, respectively, whereas a 38 to 42 C range was observed for other lactobacilli. Cell-free extract of L. cellobiosis was studied for transgalactosylase activity. When incubated with melibiose, a new compound was detected and tentatively identified as manninotriose.